2011
DOI: 10.1016/j.ajog.2011.02.071
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 overexpression in vivo blocks hyperglycemia-induced specific PKC isoforms: substrate activation and consequent lipid peroxidation in diabetic embryopathy

Abstract: Objective Oxidative stress plays a causative role in diabetic embryopathy. We tested whether mitigating oxidative stress, using superoxide dismutase 1 (SOD1) transgenic mice, would block hyperglycemia-induced specific PKC isoform activation and its downstream cascade. Study Design Day 8.5 (E8.5) embryos from non-diabetic WT control (NC), diabetic mellitus WT (DM) and diabetic SOD1-Tg mice (DM-SOD1-Tg) were used for detection of phosphorylated (p-) PKCα/βII and p-PKCδ, and levels of two prominent PKC substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…This appears to occur by reduction of LPO levels and diminished expression of the cellular lipidperoxidation marker, 4-HNE, and nitrosative stress marker, nitrotyrosine. Our previous studies have indicated that oxidative stress is a causal event in the induction of diabetic embryopathy 3, 18 . This present work confirms previous observations that curcumin inhibits diabetes-induced superoxide production, a major agonist of oxidative stress 13 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This appears to occur by reduction of LPO levels and diminished expression of the cellular lipidperoxidation marker, 4-HNE, and nitrosative stress marker, nitrotyrosine. Our previous studies have indicated that oxidative stress is a causal event in the induction of diabetic embryopathy 3, 18 . This present work confirms previous observations that curcumin inhibits diabetes-induced superoxide production, a major agonist of oxidative stress 13 .…”
Section: Resultsmentioning
confidence: 98%
“…Oxidative stress is a key mechanism underlying maternal diabetes-induced NTD formation 3, 18, 19 . Maternal diabetes-induced ROS react with iNOS-induced nitric oxide to generate RNS, which cause to a severe form of oxidative stress, nitrosative stress 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy with pre-existing maternal diabetes significantly increases the risk of excess apoptosis occurs in target tissues of the developing embryos resulting in diabetes-induced birth defects, such as neural tube defects (NTDs) and congenital heart defects (CHDs) 1-8 . Each year, 10% of babies of diabetic mothers are born with a major congenital malformation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Each year, 10% of babies of diabetic mothers are born with a major congenital malformation 9 . Mechanistic studies demonstrate that maternal diabetes alters multiple cellular and metabolic factors contributing to diabetic embryopathy 1, 4, 10-13 . We propose that these cellular and metabolic aberrations occur through a single transcriptional mechanism, a transcription factor and its responsive gene, leading to apoptosis in embryonic cells.…”
Section: Introductionmentioning
confidence: 99%